(untitled) (KONFERENSIYA, 2025)
Emotional speech in literary characters’ dialogue constitutes a crucial expressive layer through which authors encode psychological states, interpersonal relationships, and ideological positions. Translating such emotionally charged discourse presents a complex challenge, as emotional meaning is embedded not only in lexical units but also in syntactic structures, pragmatic markers, cultural conventions, and stylistic devices. This study explores the role of translation models such as operational model, linguistic model, communicative-pragmatic models and translation strategies in the transfer of emotional speech in literary characters. Employing a qualitative comparative methodology informed by equivalence-based, communicative, functionalist, and pragmatic translation theories, the research examines how emotional meaning is preserved, transformed, or compensated in translation. The findings indicate that emotional fidelity can only be achieved through an integrative application of translation models combined with flexible strategies such as modulation, adaptation, compensation, and pragmatic substitution. The article argues that emotional adequacy should be regarded as a fundamental criterion in evaluating literary translation quality